Identification of gas outburst precursors based on outburst percolation theory - Yulin Ma; Mingyu Chen (Scientific Reports)
Abstract Uniaxial compression experiments were conducted on coal rock utilizing a computed tomography (CT) scanning system for real-time monitoring to explain the issue of gas volume significantly exceeding reservoir capacity during coal and gas outbursts. A percolation factor a which can make a significant contribution to the research on premonitory information of gas outbursts is introduced to determine whether percolation occurs in coal rock, and supports the outburst percolation theory. It was found that percolation probability and correlation length increase with greater porosity, and that the number of pore clusters decreases as porosity increases. All three parameters exhibit explosive increases or decreases before the porosity reaches the percolation threshold. The percolation threshold for the coal varies at different stress levels; as the coal approaches its stress limit, the percolation threshold decreases, making percolation transformation more likely to occur and increasing the risk of a coal and gas outburst. When a > 1, percolation transformation occurs within the coal, and large-scale gas migration channels are formed. This stage completes the latent phase of the outburst, significantly elevating the likelihood of an outburst incident. This approach establishes quantitative relationships between porosity and various percolation parameters at different stress levels. It contributes to the research on precursory information of coal and gas outbursts.